2012
DOI: 10.5430/ijba.v3n2p2
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Quality and Cost of Equity in Financial Companies

Abstract: There are many studies demonstrating how good corporate governance positively affects the economic-financial performance of companies, but few which examine the relationship between corporate governance and cost of equity capital. These mainly focus on multiple industries, and suggest that there are positive shareholder value implications for firms with stronger corporate governance mechanisms.
This paper investigates the relationship between the quality of governance and the cost of equity in financial …
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
9
5
0
Order By: Relevance
“…Institutional investors will then be less likely to play their monitoring role of managerial opportunism (Villalonga and Amit, 2006). The result is consistent with that found by Regalli and Soana (2012). In the Tunisian context, Shabou (2003) concludes that the degree of participation of financial institutions in the firm's capital has a significantly negative impact on its performance.…”
Section: Ownership Structure and Cost Of Equity Capital: Linear Vs Nonlinear Relationshipssupporting
confidence: 57%
See 1 more Smart Citation
“…Institutional investors will then be less likely to play their monitoring role of managerial opportunism (Villalonga and Amit, 2006). The result is consistent with that found by Regalli and Soana (2012). In the Tunisian context, Shabou (2003) concludes that the degree of participation of financial institutions in the firm's capital has a significantly negative impact on its performance.…”
Section: Ownership Structure and Cost Of Equity Capital: Linear Vs Nonlinear Relationshipssupporting
confidence: 57%
“…Their results showed that after the financial crisis, family control is linked to a higher cost of equity capital. Regalli and Soana (2012) find that financial firms with good internal and external governance have a high cost of equity capital. They argue that companies with significant institutional investment are those for which shareholders require a high cost of equity capital.…”
Section: Ownership Structure and Cost Of Equity Capital Under The Entrenchment Thesismentioning
confidence: 97%
“…Therefore, our results are consistent with the Agency's theory of separation of the chairman board and executive director, these results are consistent with the findings of Afkhami Rad (2014) and Asadi and Mohammadzadeh (2016). Institutional ownership (+H7) has a significant positive effect on the COE, our results supported the findings of Ashbaugh et al (2004), Ali Shah and Butt (2009), Regalli and Soana (2012), Bozec and Bozec (2010), Asadi and Mohammadzadeh (2016), and same results with leverage (+H9), the research finding supported by Zhu (2014), Houqe et al (2017). It is appeared where creditors feel the risk of liquidation or merger when there is a large proportion of institutional ownership.…”
Section: Discussion Of Research Findingssupporting
confidence: 90%
“…Institutional ownership (+H7) has a significant positive association with the COE. These results are same as Ashbaugh et al (2004), Ali Shah & Butt (2009), Regalli and Soana (2012), Bozec and Bozec (2010), Asadi and Mohammadzadeh (2016). As well as leverage (+H9) is the same results of Zhu (2014), Houqe et al (2017).…”
Section: Discussion Of Research Findingssupporting
confidence: 86%
“…Another critical point is that COE was found in that study was 29 percent which is much high than the average COE of America that is around 13 percent and higher than other studies as well (Huang et al, 2009;Regalli and Soana, 2012). Shah and Butt (2009) stated that there is heterogeneity among the different sectors of Pakistan.…”
Section: Introductionmentioning
confidence: 66%